The role of the healthcare agent in comparative perspective (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The essay analyzes the role of the healthcare agent in some European civil law and common law legal systems. The comparative analysis will highlight the peculiarities of the regulation of this institute in each of the jurisdictions examined, which assigns the healthcare agent the delicate task of interacting with physicians if the patient is incapable of deciding on medical treatments. The powers proper of the "Betreuer" in Germany, the "Attorney" in England, and the "Personne de confiance" in France do not coincide perfectly with the Italian comparable, configuring a different legislative balance between patient's autonomy and physicians' will.
Keywords: Advance care planning; shared care planning; advance decisions; healthcare agent; patient autonomy